2022
DOI: 10.1088/1755-1315/995/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rhizobium Inoculation On The Growth Of Rice (Oryza Sativa L.) and White Radish (Raphanus Sativus L.)

Abstract: The utilization of chemical fertilizers in agriculture production could cause harmful effects on human health and the environment, therefore the development and application of biofertilizers produced from beneficial microorganisms like plant growth-promoting rhizobacteria have been increasingly encouraged. The present study investigated the effects of the inoculation of the two Rhizobium pusense strains (R. pusense GCB108 and R. pusense GCB117) on the growth of the young rice plant (Oryza sativa L.) and white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Rhizobium pusense colonize mungbean roots and improve plant growth by producing phytohormones ( Chaudhary et al, 2021 ). Similarly, Nguyen et al (2022) demonstrated the occurrence of Rhizobium pusense in rice and increased its growth and yield upon inoculation. Members of genus Bradyrhizobium dominantly exist in the roots and nodules of mungbean and soybean.…”
Section: Resultsmentioning
confidence: 95%
“…Rhizobium pusense colonize mungbean roots and improve plant growth by producing phytohormones ( Chaudhary et al, 2021 ). Similarly, Nguyen et al (2022) demonstrated the occurrence of Rhizobium pusense in rice and increased its growth and yield upon inoculation. Members of genus Bradyrhizobium dominantly exist in the roots and nodules of mungbean and soybean.…”
Section: Resultsmentioning
confidence: 95%
“…The use of biofertilizers is known to increase macronutrient and micronutrient absorption (Nadarajah, 2017). Nguyen et al, (2022) reported the importance of the co-inoculation of specific microbes in soil quality maintenance and plant growth. Biofertilizer inoculation has been shown to improve plant N uptake and enhance several physiological aspects of plant performance.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, several authors are studying the runoff regime and sediments in the lower reaches of the SG-DN River [7][8][9][10]. These studies have shown that the area is highly sensitive to climate change, sea level rise, and land use.…”
Section: Introductionmentioning
confidence: 99%